DAMPAK PEREKONOMIAN PENGGUNAAN TENAGA KERJA ASING DI LOMBOK TIMUR - Ahmad Rosidi (Akuntansi research UGR, 2019)
This writing aims to find out 1) What factors are behind the increasing number of foreign workers in the East Lombok Region. 2) what is the effort of the East Lombok Regency Government to protect local workers from the rush of foreign workers in the East Lombok Regency. This research was conducted with the